Report on the 37th Congress of the Polish Psychological Association “Psychology today – challenges and opportunities” Łódź, 18–20 September 2025 - Bielawska-Batorowicz, Eleonora; Znajmiecka, Marta (Przegląd Psychologiczny, 2025)
Abstract